THE IMPLEMENTATION OF CODE STEMI PROGRAM TO AFFECT THE QUALITY OF HEALTHCARE IN ST-ELEVATION MYOCARDIAL INFARCTION (STEMI) PATIENTS: A SYSTEMATIC LITERATURE REVIEW - Ginanjar, Eka; Sjaaf, Amal C (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Backgrounds: The Clinical importance of coronary artery disease manifests as Acute Coronary Syndrome with the highest mortality is known as ST-Elevation Myocardial Infarction (STEMI). Delay in STEMI management not only affect mortality and complications, but also healthcare quality. The CODE STEMI program was developed to shorten the time and reduce delay in treatments for STEMI patients. This study aims to review the effect of CODE STEMI program implementation on clinical outcome and healthcare quality in STEMI patients. Methods: This study was a systematic review of literature that used meta-analysis (PRISMA) protocol. Data obtained from Electronic databases Google Scholar, PubMed, and MEDLINE that published over several years and we began on May 2019. Assessment of healthcare quality was based on Donabedian theory that consists of 7 main components, efficacy, effectiveness, efficiency, optimality, acceptability, legitimacy and equity. Analysis between studies was reported as descriptive narration. Results: The search found 15 studies, of which 4 studies as the final results that are suitable for this literature review through the keyword findings CODE STEMI, STEMI, and quality of healthcare. Studies in several countries over the globe reported a decrease of door-to-balloon/ diagnosis-to-wire time. Some studies reported reduced mortality, complications, and cost after implementation of CODE STEMI program, while others only found insignificant trends. Conclusions: Implementation of CODE STEMI protocol made a better Quality of Healthcare. However, it needs further study to review and evaluate the effect of CODE STEMI implementation, especially on the quality of healthcare in STEMI patients.